OA Article Charges: Good Business, Bad Business, or Just More Business? - Scott Warren (Issues in Science and Technology Librarianship)
The author argues that it is not cost-effective for libraries to pay open access (OA) article charges. The author explains how OA charges will become a supplementary cost for libraries if they decide to pay for individual articles authored on their campus to be published OA. The author suggests a prudent approach for libraries to support OA initiatives.